The Sustainability of Renewable Energy Consumption in South Africa - Beşer, Nazife Özge; Beşer, Murat (International Journal of Contemporary Economics and Administrative Sciences, 2021)
Renewable energy sources are essential in reducing carbon emission levels and promoting a global green economy. The aim of this study was to examine the sustainability of renewable energy consumption per capita in Africa by using the annual data for the period 1965-2018. For this purpose, in addition to traditional unit root tests, various unit root tests taking into account different structural changes were utilized in the study. According to the obtained results, the renewable energy consumption series in Africa was found to be stable. Thus, it was concluded that sustainability was valid because the effects of one-unit shocks in energy use were not permanent..